Photography and Archive Fever in Richard Kalinoski’s Beast on the Moon (1995) - Laurence Petit (Sillages Critiques)
Drawing from critics such as Jacques Derrida, Janine Altounian, and Melanie Klein, this essay examines the close links between photography, family, and traumatic suffering in their relation with the notions of “archive”, “survivance” (as opposed to “survival”), “reparation”, and “re-membrance”. The play, which addresses the 1915 Armenian genocide, revolves around an object which, along with an old coat, works as the one and only familial “archive”, namely a central family photograph whose heads were actually cut out by Aram Tomasian after he witnessed the terrible massacre of his entire Armenian family and fled to America. The family portrait, which in the course of the play suffers both a decapitation and an indirect crucifixion but somehow manages to survive, becomes the repository not just of individual destinies – or of one individual’s destiny – but of the diasporic fate of a whole people, the Armenians.